Social-pedagogical accompaniment of foreign students’ socialization: the experience of practical realization in educational-cultural environment of a higher educational institution - Bilyk, Olena (ScienceRise: Pedagogical Education, 2017)
The analysis of the features of introduction of the social-pedagogical accompaniment of foreign students’ socialization in educational-cultural environment of a higher educational institution is realized in this article. There is offered to consider the social-pedagogical accompaniment of foreign students’ socialization as a type of social-pedagogical activity, directed on their protection, help and support in the process of acculturation by interaction of accompanied person (foreign student) with accompanying person (social pedagogue, tutor, dean’s office worker, professor or other person, who realizes the accompaniment), which results are in creation of the optimal conditions for the effective development of their sociality (intercultural and social-professional components). The directions of the social-pedagogical accompaniment realization are explained in the context of necessity of strengthening attention to foreign students’ socialization in HEI educational-cultural environment under conditions of higher education internationalization: – Activity on training of environment representatives for the effective intercultural interaction with foreign students; – activity on training of foreign students for self-organization in HEI educational-cultural environment; – support of self-organization and self-education of foreign students as to the development of intercultural and social-professional components of their sociality. The organizational forms of realization of social-pedagogical accompaniment directions are considered: seminars, round tables, master-classes, lectures-presentations, evenings, trainings, cultural assimilators, art-therapy, virtual excursions and so on. The attention is concentrated of the features of accompaniment introduction at different stages as to the work with foreign students as objects of accompaniment: adaption-motivational, integration-activity, individualization-self-realization as, correspondingly, social-pedagogical protection, socio-pedagogical help and support. The material of this article may be used in the work practice as to realization of social education of foreign students, direction of efforts of higher educational institutions on the increase of quality of foreign students’ training in Ukraine